Higher social class is associated with higher contextualized emotion recognition accuracy across cultures - Konstantinos Kafetsios; Ursula Hess; Itziar Alonso-Arbiol; Astrid Schütz; Dritjon Gruda; Kelly Campbell; Bin-Bin Chen; Daniel Dostal; Marco J. Held; Petra Hypsova; Shanmukh Kamble; Takuma Kimura; et al. (PLoS ONE, 2025)
We tested links between social status and emotion recognition accuracy (ERA) with participants from a diverse array of cultures and a new model and method of ERA, the Assessment of Contextualized Emotion (ACE), which incorporates social context and is linked to different types of social interaction across cultures. Participants from the Czech Republic (Study 1) and from 12 cultural groups in Europe, North America, and Asia (Study 2) completed a short version of the ACE, a self-construal scale, and the MacArthur Subjective Social Status (SSS) scale. In both studies, higher SSS was associated with more accuracy. In Study 2, this relationship was mediated by higher independent self-construal and moderated by countries’ long-term orientation and relational mobility. The findings suggest that the positive association between higher social class and emotion recognition accuracy is due to the use of agentic modes of socio-cognitive reasoning by higher status individuals. This raises new questions regarding the socio-cultural ecologies that afford this relationship.